Kemampuan Manajerial Kepala Madrasah, Iklim Madrasah dan Mutu Madrasah di Kecamatan Panyabungan Kabupaten Mandailing Natal - Ali Masran Daulay (Journal Of Administration and Educational Management (ALIGNMENT), 2023)
This study aimed to describe the managerial capabilities of madrasa heads, madrasah climate, and madrasah quality in Panyabungan District and to analyze how much influence it had both partially and simultaneously. This study used a quantitative approach with descriptive methods; this type of survey research and regression analysis were conducted at 48 madrasahs with 285 teachers and 48 madrasa heads. The number of samples was ten madrasahs with ten madrasa heads and 78 teachers who were taken using Proportionate stratified random sampling. Based on the results of data processing and analysis, it was found that the managerial capabilities of madrasah heads, madrasah climate, and madrasah quality in madrasas in the Panyabungan District were in the very high category. The results showed that the managerial ability of the madrasah principal had a significant positive effect on the quality of the madrasah, the climate of the madrasah had a positive and significant impact on the quality of the madrasah, and together the managerial ability of the madrasah principal and the climate of the madrasah had a significant positive effect on the quality of the madrasah. In conclusion, the Managerial Capabilities of madrasah heads and madrasah climate are important factors that must be built to achieve madrasah quality, especially in the controlling aspect, the madrasah health climate aspect, and the output aspect. Keyword primarily on controlling aspects, aspects of madrasah health climate, and output aspects.